Evaluation of Audit Quality Control at the Surakarta City Inspectorate - Leonardo Gilang Indra Nugraha; Dewi Kartikasari; Daniel Budi Pratama (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Audit quality control is required to ensure and provide the assurance of audits that had applied with auditing standards and code of ethics.. The Government Internal Supervisory Appartus (APIP) considered the three lines model functions to provide independent for objective assurance and advice on all matters related for the achievement of organizational goals. Therefore, APIP is obliged to apply the Guidelines for Quality Control Audit of Government Internal Supervisory Apparatus. This research aims to analyze the suitability of the implementation of audit quality control at the Surakarta City Inspectorate using the eight elements contained in the APIP Pedoman Kendali Mutu APIP dan Pedomaan Telaah Sejawat, and to analyze the strategies implemented for improving audit quality controls at the Surakarta City Inspectorate. The research methodology used a case study-based on qualitative descriptive method. The data used in this study are primary data, which obtained through interviews with source person and secondary data from 32 documents. The results of data analysis indicated, that the audit implementation at the Surakarta City Inspectorate had not been fully implemented the APIP Auditi Quality Control Guidelines. The strategy needs for improving the effectiveness of the implementation of audit quality control are the commitment of the leadership and all employees to enforce the supervision in according with PKMA-APIP.